Different effects of myotoxins bothropstoxin-I and II from Bothrops snake venom on cation transport ATPases from murine fast twitch skeletal muscle. (1st September 2015) - Ayres, Rodrigo; Feijó, Priscilla R.O.; Cintra, Adelia C.O.; Tomaz, Marcelo A.; Melo, Paulo A.; Cunha, Valéria M.N.; Quintas, Luis Eduardo M.
Abstract: Bothrops jararacussu venom drastically decreases sarcoplasmic Ca 2+ -ATPase (SERCA) protein expression in vivo and inhibits its activity in vitro, in contrast to a slight increase of Na + /K + -ATPase expression in murine EDL. We investigated the effect of myotoxins bothropstoxin-I and/or -II (BthTX-I, BthTX-II and BthTX-I+II) on this model. No changes were seen in SERCA1, SERCA2 and Na + /K + -ATPase α1 protein expression as well as 2+ Ca-ATPase activity, but BthTX-II (1 μg/g) reduced Na + /K + -ATPase α2 expression by 50% one day after perimuscular injection. Interestingly, BthTX-II inhibited Ca 2+ -ATPase activity (IC50 around 6 nM). Our findings suggest that only BthTX-II affects ion transport ATPases, being a potent SERCA inhibitor and a putative target for antivenom drug development. Graphical abstract: Highlights: Bothropstoxin-I and -II effects on mouse EDL Ca 2+ - and Na + /K + -ATPase were studied. Ca 2+ -ATPase protein isoforms expression and activity were not affected. Na + /K + -ATPase α2, but not α1, protein expression was decreased by bothropstoxin-II. Bothropstoxin-II potently inhibited Ca 2+ -ATPase activity in vitro .